Cardioprotective effects of exercise training on doxorubicin-induced cardiomyopathy: a systematic review with meta-analysis of preclinical studies - Paola Victória da Costa Ghignatti; Laura Jesuíno Nogueira; Alexandre Machado Lehnen; Natalia Motta Leguisamo (Scientific Reports, 2021)
Abstract Doxorubicin (DOX)-induced cardiotoxicity in chemotherapy is a major treatment drawback. Clinical trials on the cardioprotective effects of exercise in cancer patients have not yet been published. Thus, we conducted a systematic review and meta-analysis of preclinical studies for to assess the efficacy of exercise training on DOX-induced cardiomyopathy. We included studies with animal models of DOX-induced cardiomyopathy and exercise training from PubMed, Web of Sciences and Scopus databases. The outcome was the mean difference (MD) in fractional shortening (FS, %) assessed by echocardiography between sedentary and trained DOX-treated animals. Trained DOX-treated animals improved 7.40% (95% CI 5.75–9.05, p < 0.001) in FS vs. sedentary animals. Subgroup analyses revealed a superior effect of exercise training execution prior to DOX exposure (MD = 8.20, 95% CI 6.27–10.13, p = 0.010). The assessment of cardiac function up to 10 days after DOX exposure and completion of exercise protocol was also associated with superior effect size in FS (MD = 7.89, 95% CI 6.11–9.67, p = 0.020) vs. an echocardiography after over 4 weeks. Modality and duration of exercise, gender and cumulative DOX dose did were not individually associated with changes on FS. Exercise training is a cardioprotective approach in rodent models of DOX-induced cardiomyopathy. Exercise prior to DOX exposure exerts greater effect sizes on FS preservation.